2015
DOI: 10.1098/rsif.2015.0827
|View full text |Cite
|
Sign up to set email alerts
|

The microscopic network structure of mussel ( Mytilus ) adhesive plaques

Abstract: Marine mussels of the genus Mytilus live in the hostile intertidal zone, attached to rocks, bio-fouled surfaces and each other via collagen-rich threads ending in adhesive pads, the plaques. Plaques adhere in salty, alkaline seawater, withstanding waves and tidal currents. Each plaque requires a force of several newtons to detach. Although the molecular composition of the plaques has been well studied, a complete understanding of supra-molecular plaque architecture and its role in maintaining adhesive strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 39 publications
(56 reference statements)
3
77
1
Order By: Relevance
“…The lack of the characteristic nanostructure in the highly cohesive (and adhesive) mfp-3S-pep SCC phase (inset in Figure 4d), compared to the mfp-3F-pep/HA CC phase (inset in Figure 4b) is intriguing, since it suggests that efficient energy dissipation and adhesion at the micrometer length scale can be achieved without, or prior to, formation of the intricate load-bearing structures at the nanometer to sub-micrometer scale that are typically observed in mature mussel plaques, including filaments or mesh structures. 11 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of the characteristic nanostructure in the highly cohesive (and adhesive) mfp-3S-pep SCC phase (inset in Figure 4d), compared to the mfp-3F-pep/HA CC phase (inset in Figure 4b) is intriguing, since it suggests that efficient energy dissipation and adhesion at the micrometer length scale can be achieved without, or prior to, formation of the intricate load-bearing structures at the nanometer to sub-micrometer scale that are typically observed in mature mussel plaques, including filaments or mesh structures. 11 …”
Section: Resultsmentioning
confidence: 99%
“…The relevance of this emphasis was brought into question by the recent discovery that interfacial chemistry provides less than 0.01% of the adhesion energy contributed by plaque geometry and architecture in whole plaques 10,11 . Here, we look beyond interfacial chemistry at the molecular scale from mussels and sandcastle worms that exploit spontaneous condensation of charged polypeptides by liquid-liquid phase separation or coacervation into complex liquids to form underwater adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Following induction, a fibrous structure can be detected in the groove which was further analyzed using several techniques . While this so‐called induced thread is morphologically impaired due to the harsh KCl injection, which paralyzes the mussel foot, it provides a means of studying the aspects of byssus formation that depend on spontaneous self‐assembly . Indeed, certain structural features similar to the native thread are achieved via induction, indicating that self‐assembly drives much of the formation process .…”
Section: Byssus Bio‐fabricationmentioning
confidence: 99%
“…Protein vesicles in the plaque gland are secreted via a complex system of small channels called longitudinal ducts in a temporally regulated fashion by which certain proteins responsible for interfacial adhesion are secreted first, whereas others follow later . The complex micro‐ and nano‐porous structure of the plaque is observed shortly after induced secretion, suggesting a quick and dramatic transition from a dense, fluid protein phase to an open‐cell foam (Figure B,E) . It has been suggested that the adhesive proteins are stored as coacervates, which then spontaneously transition to a solid due to the local physiochemical environment (pH, salt concentration) .…”
Section: Byssus Bio‐fabricationmentioning
confidence: 99%
“…[1] Although previous studies using catechol-decorated polymers have demonstrated improvements in adhesion, [5,12,16] the performance of such manmade polymers, [16] as well as isolated native mussel and engineered proteins [17] is still far lower than that of whole natural mussel plaques, in terms of the total energy required to dislodge a plaque from a surface. [18] These differences may arise from the lack of consideration given in previous work to the heterogeneous nature of the mussel plaque structures [19] and their impact on load transfer within the material. For example, although catechol residues are highly enriched (20–28 mol%) in interfacial mfps, they are much less abundant in bulk mfps (2–5 mol%).…”
mentioning
confidence: 99%